2021
DOI: 10.3928/00220124-20210414-05
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Evidence-Based Sepsis Care: A Sepsis Escape Room

Abstract: Background: Using evidence-based sepsis guidelines, nurse educators identified the nursing skills required to recognize and treat sepsis. Method: Nurse educators created an innovative, interactive sepsis escape room to provide sepsis education. The escape room included a manikin, puzzles, distractors, riddles, and props. Participants were given 20 minutes to solve four puzzles/riddles to treat the sepsis patient and escape the room. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…Many nursing tasks cannot be performed by oneself; they require cooperation with other nurses and other disciplines, such as doctors and technicians. Good teamwork performance can increase the quality of nursing and can increase patient outcomes [31]. The results showed that the attitudes toward teamwork were signi cantly different before and after the escape room training in terms of the total score and for the following dimensions: team structure, leadership, situation monitoring, mutual support, and communication.…”
Section: Discussionmentioning
confidence: 95%
“…Many nursing tasks cannot be performed by oneself; they require cooperation with other nurses and other disciplines, such as doctors and technicians. Good teamwork performance can increase the quality of nursing and can increase patient outcomes [31]. The results showed that the attitudes toward teamwork were signi cantly different before and after the escape room training in terms of the total score and for the following dimensions: team structure, leadership, situation monitoring, mutual support, and communication.…”
Section: Discussionmentioning
confidence: 95%
“…The educator will likely have to play this role within school organizations. Thus, educators should be informed of learner-centered innovative teaching methods that reflect the learning styles and preferences of students [25][26][27], and offer support through teaching delivery media, both online and offline [28,29]. Above all, a regular EBP competency-building program for educators may need to be implemented to foster positive attitude, knowledge, and skills pertaining to EBP training among other members of the staff [30,31].…”
Section: Discussionmentioning
confidence: 99%